Vitamin D deficiency and alterations in the glycidic profile of belonging to type II diabetics: An integrative literature review (Research, Society and Development, 2021)
Observational studies have shown a relationship between vitamin D deficiency in the blood and worsening type II diabetes mellitus. Thus, this study aimed to verify the relationship of vitamin D deficiency with changes in the glucose profile of individuals with type II diabetes mellitus. For this, an integrative literature review was carried out, in which a sequence of six steps was adopted: elaboration of the research question, data extraction, evaluation of the primary studies included, analysis and synthesis of the results and presentation of the review. And, among the adopted inclusion criteria, the articles published in the last five years stand out, covering the period from 2016 to 2021; original articles, studies carried out with individuals of both sexes, aged over 20 years, different ethnicity and socioeconomic status, whose languages ​​were in Portuguese, English and Spanish, with access to the full text, using the Latin Literature databases. American and Caribbean in Health Sciences (LILACS), Pubmed and Web of Sciense for article searches. The present review resulted in 05 articles included, of which 04 studies revealed the relationship between serum vitamin D levels with the glucose profile of patients with type II diabetes mellitus, especially in relation to fasting plasma glucose. Therefore, we can conclude that vitamin D deficiency is a public health problem and that its deficiency can result in alterations in the glycidic profile of individuals with type II diabetes.